APLIKASI PASTA GIGI HERBAL DAN NON HERBAL DALAM MENURUNKAN SKOR PLAK DAN MENINGKATKAN KETERAMPILAN MENYIKAT GIGI PADA ANAK USIA 6-15 TAHUN DI DESA MUARO JAMBI TAHUN 2023 - riyadi, slamet; Halid, Idham; Rosmawati, Rosmawati (Poltekkes Kemenkes Jambi, 2023)
ABSTRAC The initial survey carried out in Muaro Jambi Village, Muaro Jambi Regency, looked at the distance between the school and the health center, namely 10 KM along a winding cement road on the edge of the Batanghari River. Public interest in having dental check-ups at community health centers is still lacking. The average occupation of people in Muaro Jambi village is farmers and plantation workers. The results of a survey of 10 children showed that 90% of children had dental caries. The approach is to seek local government policy support, namely stakeholders in Muaro Jambi village, Jambi Kecil Community Health Center, Head of the Muaro Sebo sub-district education service, with the aim of increasing student participation facilitated by class teachers at each school, holding meetings with the Head of Muaro Jambi village and his staff. , holding meetings with principals of SDN, Madrasah and MTS, informing work plans and activity schedules to be agreed and adapted to partner conditions and situations and conducting evaluations of activities Increase in students' understanding of how to brush their teeth properly and correctly before counseling with an average plaque score of 12-13 teeth showing disclosing staining stains for each student, to an average of 1-2 teeth showing disclosing staining stains for each child After counseling, there was an increase in tooth brushing skills and can be seen from the plaque score results - an average of 1-2 teeth visible disclosing staining. There has been an increase in skills on how to brush teeth, which can be seen from the reduction in dirty teeth before the activity to an average of 12-13 dirty teeth and after intervention to an average of 1 to 2 teeth for each student.